Study endoscopic and colonoscopy findings in children under 16 years of age with gastrointestinal bleeding from 2018 to 2021 - Ajri Khamesloo, Faramarz; Mardi, Ali; Kamran, Aziz; Pourasghar, Abdolvahid (International Journal of Research in Medical Sciences, 2024)
Background: One of the most common reasons for Children to visit clinics is gastrointestinal issues in which endoscopic studies are used occasionally to investigate it’s etiology more accurately. GI bleeding eventhough uncommon in children, can be life threatening. The aim of this study was to study endoscopic and colonoscopic findings in children with GI bleeding. Methods: This descriptive analytical study was done on 73 children under 16 years in Ardabil with the diagnosis of gastrointestinal bleeding. A checklist including demographic and treatment information of patients like severity of bleeding, bleeding type (melena, hematochezia, occult blood), laboratory results (hemoglobin, hematocrit) and clinical findings (abdominal pain, nausea and vomiting, ETC), endoscopic and colonoscopic results were collected and then analyzed by statistical methods in SPSS version 21. Results: Total 38 cases (52.1%) were gone under upper endoscopy and 35 cases (47/9%) were gone under colonoscopy. The most common indications for upper endoscopy was GI bleeding (76.3%) and the most common involved anatomical part was lower portion of esophagus (44.7%). The most common indication for colonoscopy was recurrent abdominal pain (62.9%). Pathologic cases were often seen in sigmoid, rectum and anus (52/8%). The most common colonoscopic findings were nodular hyperplasia (25/7%) and solitary nodule (20%). Conclusions: Results of study showed that, the frequency of endoscopic evaluation has been significantly lower in female children. According to the most common indications for upper and lower endoscopy, it is important to consider the frequency pattern of indications for endoscopic study.